2008
DOI: 10.1002/mame.200800120
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Tunable Submicro‐ or Nano‐Structured Polyethylene Materials from Immiscible Blends with Cellulose Acetate Butyrate

Abstract: Low density polyethylene (LDPE) was prepared into micro‐ or submicro‐spheres or nanofibers via melt blending or extrusion of cellulose acetate butyrate (CAB)/LDPE immiscible blends and subsequent removal of the CAB matrix. The sizes of the PE spheres or fibers can be successfully controlled by varying the composition ratio and modifying the interfacial properties of the blends. The surface structures of LDPE micro‐ or submicro‐spheres and nanofibers were analyzed using SEM and FTIR‐ATR spectroscopy. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…We were unable to completely disperse PE‐ co ‐AA30 nanofibers by using the above stated method, and they appeared as larger bundles of fibers. This observation was similar to what have been previously observed from poly(ethylene‐ co ‐glycidyl methacrylate) 38. The more dilute the PE‐ co ‐AA copolymer in CAB matrix, the smaller the copolymer droplets formed during melt blending, resulting in finer and discontinuous nanofibers.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We were unable to completely disperse PE‐ co ‐AA30 nanofibers by using the above stated method, and they appeared as larger bundles of fibers. This observation was similar to what have been previously observed from poly(ethylene‐ co ‐glycidyl methacrylate) 38. The more dilute the PE‐ co ‐AA copolymer in CAB matrix, the smaller the copolymer droplets formed during melt blending, resulting in finer and discontinuous nanofibers.…”
Section: Resultssupporting
confidence: 90%
“…PE‐ co ‐AA nanofibers were prepared according to a procedure previously reported 35, 38. Two components, usually PE‐ co ‐AA and cellulose acetate butyrate (CAB), were fed into and blended in ratios of 10/90, 20/80, and 30/70 in a Leistritz corotating twin‐screw (18 mm) extruder (Model MIC 18/GL 30D, Nurnberg, Germany) at 240°C.…”
Section: Methodsmentioning
confidence: 99%
“…The past decades have witnessed a rapid development of researches on polymer blends, which has lead to a broad variety of applications,1–9 Investigations including miscibility, phase behavior, microstructure, crystallization, hierarchical morphology, and physical and mechanical properties have been detailed 1–3, 8–13. Recently, a novel process of producing submicron and nanosized thermoplastic fibers in continuous yarn forms was developed through polymer blending method 14–18. By selectively removing a sacrificial polymer matrix of cellulose acetate butyrate (CAB) from melt extruded well mixed immiscible blends, thermoplastic polymers such as isotactic polypropylenes (iPP),14, 17 poly(trimethylene terephthalate),14, 15 polyethylene‐ co ‐(glycidyl methacrylate),14, 18 and low‐density polyethylene16 have been fabricated into nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the diameter distributions of iPP nanofibers were mainly from 100 to 500 nm while PP‐g‐MAH nanofibers from 200 to 500 nm. Previous work15 has found that the factors, such as weigh ratio, viscosity ratio, drive speed, etc., would affect the size of thermoplastic nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…However, the thermoplastic polymer nanofibers were rarely prepared by electrospinning because of their high viscosity. On the other hand, in‐situ fibrillar blends can provide a method to a high throughput process that can prepare PP, polyethylene, poly (ethylene‐co‐(glycidyl methacrylate)), and poly (ethylene terephthalate) nano‐scale fibers 15–19. This method involves choosing two kinds of immiscible thermoplastic polymers, mixing and extruding them from a co‐rotating twin screw extruder, after removing the matrix phase, and finally nanofibers can be obtained.…”
Section: Introductionmentioning
confidence: 99%